Tax havens and transfer pricing intensity: Evidence from the French CAC-40 listed firms - Ronan Merle; Bakr Al-Gamrh; Tanveer Ahsan (Cogent Business & Management, 2019)
Multinational enterprises (MNEs) may use transfer pricing techniques and policies to reduce their tax base in higher-tax rate jurisdictions by shifting it to lower-tax rate countries or tax havens. These practices, enhanced by the globalization and dematerialization of the economy, have flourished and became a major issue for supranational organizations, tax authorities and even in the public opinion. This study analyses the impact of intangible assets, firm size, effective tax rate, and leverage on transfer pricing intensity. French publicly listed firms in the CAC-40 were examined during the period from 2012 to 2015. The regression results show that the firm size and leverage are positively associated while intangible assets and effective tax rate are negatively associated with transfer pricing intensity.
Keywords: 650; transfer pricing intensity; effective tax rate; intangible assets; firm size; leverage